Improving our understanding of the most important items of the Multiple Sclerosis Walking Scale-12 indicating mobility dysfunction: Secondary results from a RIMS multicenter study - Kalron, Alon; Ehling, Rainer; Baert, Ilse; Smedal, Tori; Rasova, Kamila; Heric-Mansrud, Adnan; Elorriage, Iratxe; Nedeljkovic, Una; Tachino, Andrea; Gargul, Leszek; Gusowski, Klaus; Cattaneo, Davide; et al. (Multiple sclerosis and related disorders, 2020)
BACKGROUND: The 12-item Multiple Sclerosis Walking Scale (MSWS-12) is currently the most widely validated, patient-reported outcome measure assessing patients' perception of the impact of multiple sclerosis (MS) on walking ability. To date, the majority of previous studies investigating the MSWS-12 have focused on the total score despite individual items being potentially informative. Therefore, our objective was to examine the associations between the individual items of the MSWS-12 and mobility and whether these associations depend on disability level. METHODS: Participants completed the MSWS-12, Two-Minute Walk Test (2MWT), Timed 25-Foot Walk (T25FW), Timed Up and Go Test (TUG) and the Four Square Step Test (FSST). Subsequently, they were divided into two groups according to their disability level, classified as either "mildly" or "moderately-severely" disabled. The correlation between individual items of the MSWS-12 and clinical measures of mobility were separately examined by Spearman's correlation coefficients; linear regression analyses were performed for each disability group, with/without adjusting for cognition, age and gender. RESULTS: 242 people with MS (PwMS), 108 mildly and 134 moderately-severely disabled, were included. Stronger correlations between the MSWS-12 items and mobility tests were found in the mildly disabled compared to the moderately-severely disabled group. The linear regression analysis showed that in the mildly disabled, item 9 (use of support outdoors) explained 35.4%, 30.8%, and 23.7% of the variance related to the 2MWT, T25FW and TUG, respectively. As for the moderately-severely disabled, the linear regression analysis presented a model which included item 8 (use of support indoors), explaining 31.6%, 18.0%, 20.2% and 9.5% of the variance related to the 2MWT, T25FWT, TUG and FSST, respectively. CONCLUSIONS: Items 8 and 9 of the MSWS-12 focusing on the patient's use of walking support in and outdoors, provide a robust indicator of mobility capabilities for mildly and moderately-severely disabled PwMS.
Keywords: Walking; chůze; Disability Evaluation; Time and Motion Studies; Humans; roztroušená skleróza; studie pohybu a času; lidé; posturální rovnováha; Postural Balance; Multiple Sclerosis; posuzování pracovní neschopnosti